Central African Economic and Monetary Community (CEMAC) : Staff Report on the Common Policies in Support of Member Countries Reform Programs-Press Release, Staff Report, and Statement by the Executive Director. (International Monetary Fund, 2020)
Tighter macroeconomic and financial policies helped to avert a deeper crisis, and gross external reserves increased more rapidly in recent months, largely exceeding the mid-2019 target. However, reserves are still below the level appropriate for commodityexporting economies (5 months of imports) to absorb terms of trade shocks. Fiscal consolidation has been tilted towards cuts in public investment. This, together with a lack of significant progress in structural reforms, has weighed on growth which remains too low. The outlook for 2019 and beyond foresees further improvement in regional reserves assuming CEMAC countries remain committed to their program objectives and new programs with CAR and Equatorial Guinea could start around end-2019. This outlook is subject to potentially significant risks, including: a significant slowdown in global growth and associated decline in oil prices; a deterioration in the security situation in some countries; and weaker implementation of IMF-supported programs.